Table of Content - - (Journal of Humanities & Social Sciences, 2025)
:Table of Content • Economic Life in the Islamic City during the Mamluk Era in Egypt, Syria, and Palestine (1250-1517): Feudalism, Economic Policies, and the Monetary Inflation Crisis Prof. Samir Hassan Al-Chikh Ali • The geomorphology of coastal features between South Sharm and Yanbu in the north to Ras Al-Breika in the south - the western coast of the Kingdom of Saudi Arabia using remote sensing technology Ms. Maram Hilal Al-Haisuni • Jawad Ali: A Historical Study of His Life, Works, and Methodology Asst-Lecturer. Jassib Abd Al-Amir Akab, Asst-Prof. Hamid Karimipour • Semiotics of Clothing in the Novel Tawq Al-Hamam: A Reading of Cultural and Social Symbols Co-Prof. Arwa Dawood Khomayyies • Al-Hilal’s victory over Manchester City: an analysis of Western media representations of the event and its symbolic connotations Co-Prof. Mona Mohammed Ibrahim Al-Sheddi • Contrastive Montage in Examples of Contemporary Saudi Poetry Ms. Mona Abdulrahman Alsaeed • Financial Liberalization & Economic Growth: Theoretical Overview Dr. Abubakr Eltigani Elhag